Isaac Cronin, Jay Harlow and Paul Johnson: The California Seafood Cookbook - Davidson, Alan E (Petits Propos Culinaires, 2024)
Isaac Cronin, Jay Harlow and Paul Johnson: The California Seafood Cookbook: Aris Books, Berkeley, California, 1983: 288 pp., numerous black and white illustrations, miniature bibliography, full index, clothbound $17.95, paperback, $10.95.